Soybean (Glycine max L.) isoflavones: Chemical composition and its chemometrics-assisted extraction and authentication - Florentinus Dika Octa Riswanto,, Abdul Rohman, Suwidjiyo Pramono, Sudibyo Martono (Journal of Applied Pharmaceutical Science, 2021)
Soybeans (Glycine max L.), a functional food widely consumed in Asia, has been reported as the main source of isoflavones. Phytoestrogen properties of soy isoflavones showed their activity as ligands for estrogen receptors and exhibited the estrogenic potency as reported in the previous in vitro and in vivo studies. Soy foods became most popular due to their benefits to human health and body function. The utilization of chemometrics in soybean isoflavones extraction and authentication was reported along with the increasing trends of computational analytical chemistry. A review on isoflavones contents in soybean, as well as its chemometrics-assisted extraction and authentication, is presented. This review aimed to report isoflavones contents in soybean, optimization designs for isoflavones extraction, and chemometrics algorithms for authentication purposes of soy-related products.
Keywords: Authentication, chemometrics, extraction, isoflavones, soybean.